AB0172 Usefulness of The Japanese Version of The Patient-Rated Elbow Evaluation in Patients with Rheumatoid Arthritis. (15th July 2016) - Takeshita, A.; Kaneda, D.; Horita, M.; Machida, T.; Nakahara, R.; Nasu, Y.; Hashizume, K.; Nishida, K.; Ozaki, T.
Abstract : Background: Patient self-administered questionnaires remove the possibility of observer bias, and are important instruments for the assessment of clinical outcome. The patient-rated elbow evaluation (PREE) is a joint-specific, self-administered questionnaires. Objectives: We aimed to investigate the correlation between the Japanese version of PREE (PREE-J) and other clinical parameters in rheumatoid arthritis (RA) patients before and after total elbow arthroplasty (TEA). Methods: Thirty-five elbows in 32 RA patients (M/F: 3/29) were replaced by TEA. The mean age was 62.1 (range 41–79) years at the time of surgery, the mean follow-up period was 21.5 (range 12–36) months. All patients were assessed pre- and post-operatively by PREE-J, elbow and forearm range of motion (ROM), Disease Activity Score with 28 joint using CRP (DAS28-CRP), Mayo Elbow Performance Score (MEPS), Japanese version of the Disabilities of the Arm, Shoulder and HAND (DASH-JSSH) and Health Assessment Questionnaire Disability Index (HAQ-DI). The changes of parameters after surgery were examined by Wilcoxon signed-rank test, and the correlation between PREE-J and other parameters was examined using Spearman's correlation coefficients. Results: Both pre- and post-operative PREE-J significantly correlated with DAS28-CRP, DASH-JSSH, and HAQ-DI. Significant improvement was observed after surgery in all parameters except for HAQ-DI. The mean postoperative MEPS improved from 50.3±16.4 points to 98.1±3.2 points, the average postoperative PREE-J improved from 54.7±19.3 points to 27.1±24.4 points. The correlation between PREE-J and MEPS was significant preoperatively (p<0.01), but the correlation disappeared postoperatively. The correlation between PREE-J and ROM was not significant pre- and post-operatively. Conclusions: The current study indicated that elbow evaluation by patients who underwent TEA showed significant correlation with disease activity, upper limb function and disability in daily life. It was revealed preoperative PREE-J also well correlated with MEPS, which is widely accepted evaluation system by elbow surgeons. Interestingly, PREE-J did not correlate with MEPS and ROM postoperatively. As PREE-J contains many questions about complex motions required the multiple joint function of upper extremity, it is possible PREE-J might be influenced by other joints affected by RA. MEPS (up to 100 points) evaluates pain (45), ROM (20), function (25) and instability (10) of the elbow, and reached almost perfect score by TEA. PREE-J evaluates pain and function with more detailed questionnaires than MEPS, some of them cannot be solved by a single joint surgery. Our results suggested PREE-J might be useful and wide range evaluation instrument for functional improvement of upper extremity after TEA. Disclosure of Interest: None declared